FKBP5 as a key regulator of metabolic processes in birds: Insights from chicken pectoral muscle - Pengfei Du; Xiangli Zhang; Yao Zhu; Ziyang Wang; Xuemeng Si; Huaiyong Zhang; Yanqun Huang; Wen Chen (Poultry Science)
FK506-binding protein 5 (FKBP5) is a negative regulator of the glucocorticoid response and may play an important role in regulating metabolic homeostasis in birds. However, limited information is available regarding its role in avian species. This study aimed to clarify the spatiotemporal characteristics of chicken FKBP5 and investigate the effects of exogenous stimuli on its expression. Real-time quantitative PCR (RT-qPCR) was utilized to analyze the spatiotemporal expression patterns of FKBP5 in chickens. Additionally, the impact of exogenous stimuli, including fasting, energy restriction, and insulin/pyruvate/glucose injections, on FKBP5 expression in the pectoral muscle was investigated. The results showed that FKBP5 is broadly expressed in various bird tissues, with dominant expression in insulin-sensitive tissues. The FKBP5 levels in birds are dramatically modulated during development in insulin-sensitive tissues, with the highest expression observed in striated muscle and liver at embryonic day 19 (E19) (P < 0.01). The basal level of FKBP5 in the pectoral muscle of broilers is higher than that in Silky chickens. Insulin administration leads to a rapid drop in blood glucose levels in both breeds, with a slower recovery in AA broilers (P < 0.01). However, FKBP5 expression in the pectoral muscle initially shows a slight drop, followed by a sharp increase over time after insulin administration (P < 0.01). Additionally, breed heterogeneity in FKBP5 expression was observed in the pectoral muscle upon insulin stimulation, with broilers showing stronger insulin sensitivity compared to Silky chickens. A 24-hour fasting period downregulated blood glucose levels (P < 0.01) and FKBP5 expression in the pectoral muscle of AA broilers (P < 0.01). A 30% energy restriction over three weeks slightly reduced blood glucose levels (P = 0.075) and significantly decreased FKBP5 levels in the pectoralis muscle of broilers. In addition, pyruvate increased blood glucose and pectoralis FKBP5 transcription levels at 60 min (P < 0.01), whereas glucose increased blood glucose levels but had no effect on FKBP5 expression. Overall analysis showed a negative correlation between FKBP5 expression in the pectoral muscle and blood glucose levels (ρ = −0.405, P < 0.001). In conclusion, FKBP5 is a key player in the metabolic regulation of birds, with its expression being highly dynamic and tissue-specific. Insulin regulates FKBP5 expression in pectoral muscles in a time-dependent manner, while pyruvate increases FKBP5 levels and fasting/energy restriction reduces FKBP5 mRNA expression in the pectoral muscles.